Guidelines for the treatment of autoimmune neuromuscular transmission disorders. - Skeie, G; Apostolski, S; Evoli, A; Gilhus, N; Hart, I; Harms, L; Hilton-Jones, D; Melms, A; Verschuuren, J; Horge, H (2006)
Important progress has been made in our understanding of the cellular and molecular processes underlying the autoimmune neuromuscular transmission (NMT) disorders; myasthenia gravis (MG), Lambert-Eaton myasthenic syndrome (LEMS) and neuromyotonia (peripheral nerve hyperexcitability; Isaacs syndrome). To prepare consensus guidelines for the treatment of the autoimmune NMT disorders. References retrieved from MEDLINE, EMBASE and the Cochrane Library were considered and statements prepared and agreed on by disease experts and a patient representative. The proposed practical treatment guidelines are agreed upon by the Task Force: (i) Anticholinesterase drugs should be the first drug to be given in the management of MG (good practice point). (ii) Plasma exchange is recommended as a short-term treatment in MG, especially in severe cases to induce remission and in preparation for surgery (level B recommendation). (iii) Intravenous immunoglobulin (IvIg) and plasma exchange are equally effective for the treatment of MG exacerbations (level A Recommendation). (iv) For patients with non-thymomatous autoimmune MG, thymectomy (TE) is recommended as an option to increase the probability of remission or improvement (level B recommendation). (v) Once thymoma is diagnosed TE is indicated irrespective of the severity of MG (level A recommendation). (vi) Oral corticosteroids is a first choice drug when immunosuppressive drugs are necessary in MG (good practice point). (vii) In patients where long-term immunosuppression is necessary, azathioprine is recommended together with steroids to allow tapering the steroids to the lowest possible dose whilst maintaining azathioprine (level A recommendation). (viii) 3,4-diaminopyridine is recommended as symptomatic treatment and IvIg has a positive short-term effect in LEMS (good practice point). (ix) All neuromyotonia patients should be treated symptomatically with an anti-epileptic drug that reduces peripheral nerve hyperexcitability (good practice point). (x) Definitive management of paraneoplastic neuromyotonia and LEMS is treatment of the underlying tumour (good practice point). (xi) For immunosuppressive treatment of LEMS and NMT it is reasonable to adopt treatment procedures by analogy with MG (good practice point).